1999
DOI: 10.1021/ja991365q
|View full text |Cite
|
Sign up to set email alerts
|

Can Single-Electron Transfer Break an Aromatic Carbon−Heteroatom Bond in One Step? A Novel Example of Transition between Stepwise and Concerted Mechanisms in the Reduction of Aromatic Iodides

Abstract: Single-electron transfer is often accompanied by bond cleavage or bond formation reactions converting initially formed ion radicals into radicals. Electron transfer and bond breaking may involve a transient ion radical intermediate or occur in a concerted manner, as sketched in Figure 1. 1 The question of the distinction between these two mechanisms and of the nature of the molecular factors that favor one mechanism over the other arises for thermal (electrochemical, homogeneous) 2 as well as for photoinduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
200
0
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 236 publications
(211 citation statements)
references
References 26 publications
7
200
0
4
Order By: Relevance
“…In analogy with chlorides and bromides, which have been more extensively investigated [3,33,34], we may assume a concerted DET mechanism for the aliphatic iodides 1b, 2b and 4c at both electrodes. As to the aromatic compound 6c, DET of iodobenzenes is reported to be a borderline between concerted and stepwise mechanisms, with the possibility of a passage from one mechanism to the other, depending on the reaction conditions [35]. Therefore, we may assume a borderline situation for 4−iodotoluene.…”
Section: Iodidesmentioning
confidence: 99%
“…In analogy with chlorides and bromides, which have been more extensively investigated [3,33,34], we may assume a concerted DET mechanism for the aliphatic iodides 1b, 2b and 4c at both electrodes. As to the aromatic compound 6c, DET of iodobenzenes is reported to be a borderline between concerted and stepwise mechanisms, with the possibility of a passage from one mechanism to the other, depending on the reaction conditions [35]. Therefore, we may assume a borderline situation for 4−iodotoluene.…”
Section: Iodidesmentioning
confidence: 99%
“…Carbon-halogen cleavage has been studied extensively in nonaqueous solvents for a number of substituted benzyl bromides, substituted iodobenzene, bromobenzene, and chlorobenzene derivatives [8][9][10][11][12]. The electrochemical reduction of a series of halogenated benzonitriles in DMF involves the initial one-electron reduction yielding the anion radical with a rapid loss of the halide ion to give the corresponding cyanophenyl radical [12].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we have shown that the neutral ground-state organic electron donor 1 [7,8] (Scheme 1) reduces iodoarenes [9,10] to aryl radicals [11] while the stronger donors 2 [12] and 3 [13] under milder conditions, afford aryl anions from the same substrates through transfer of two electrons. These donors also reduce sulfonamides, acyloin derivatives, and Weinreb amides.…”
mentioning
confidence: 98%
“…Thus, we have shown that the neutral ground-state organic electron donor 1 [7,8] (Scheme 1) reduces iodoarenes [9,10] to aryl radicals [11] while the stronger donors 2…”
mentioning
confidence: 99%